The gamma-tubulin ring complex: deciphering the molecular organization and assembly mechanism of a major vertebrate microtubule nucleator - Böhler, Anna; Vermeulen, Bram J. A.; Würtz, Martin; Župa, Erik; Pfeffer, Stefan; Schiebel, Elmar (Bioessays, 2021)
Microtubules are protein cylinders with functions in cell motility, signal sensing, cell organization, intracellular transport, and chromosome segregation. One of the key properties of microtubules is their dynamic architecture, allowing them to grow and shrink in length by adding or removing copies of their basic subunit, the heterodimer αβ-tubulin. In higher eukaryotes, de novo assembly of microtubules from αβ-tubulin is initiated by a 2 MDa multi-subunit complex, the gamma-tubulin ring complex (γ-TuRC). For many years, the structure of the γ-TuRC and the function of its subunits remained enigmatic, although structural data from the much simpler yeast counterpart, the γ-tubulin small complex (γ-TuSC), were available. Two recent breakthroughs in the field, high-resolution structural analysis and recombinant reconstitution of the complex, have revolutionized our knowledge about the architecture and function of the γ-TuRC and will form the basis for addressing outstanding questions about biogenesis and regulation of this essential microtubule organizer.